A Reconsideration of Two Spanish Women Poets: Angela Figuera and Francisca Aguirre - John C. Wilcox (Studies in 20th & 21st Century Literature, 1992)
In the last decade, poetry written by women in Spain experienced a "boom," as one close observer of the scene has noted, with the result that young women poets on the Peninsula have begun to receive the attention they merit. It is therefore an opportune moment to turn our critical attention toward the poetry written by women earlier in the twentieth century. Angela Figuera (1902-1984) and Francisca Aguirre (b. 1930), two "uncanonized" mid-twentieth century Spanish poets, are presented here as challenging the androcentric culture of their time. Figuera critiques the male-dominated poetic canon as she develops a gynocentric poetics; poems for which she is recognized as criticizing Spanish politics and society are read as also manifesting the vision of a marginalized woman poet who for lack of full recognition loses confidence in herself; and the positive image previous critics have found in her vision of motherhood is demystified. Aguirre—avant Gilbert & Gubar—presents the female persona in her work as reduced to near "madness" by the barren space in which she is forced to live; her minimalist philosophy deflates the grand (patriarchal) illusions of her Occident; her work demystifies androcentric Western esthetics as it inscribes within Spanish poetry a gynocentric vision (with metaphors found in other recent women poets). It is hoped that in future reassessments of the canon, the work of these poets will be given more careful perusal.
Keywords: boom; women poets; Spanish poetry; Angela Figuera; Francisca Aguirre; uncanonized literature; culture; feminism; male; female; politics; society; marginalization; motherhood; space; patriarchy; gynocentric